2022
DOI: 10.1155/2022/3905998
|View full text |Cite
|
Sign up to set email alerts
|

Breast Tumor Ultrasound Image Segmentation Method Based on Improved Residual U-Net Network

Abstract: In order to achieve efficient and accurate breast tumor recognition and diagnosis, this paper proposes a breast tumor ultrasound image segmentation method based on U-Net framework, combined with residual block and attention mechanism. In this method, the residual block is introduced into U-Net network for improvement to avoid the degradation of model performance caused by the gradient disappearance and reduce the training difficulty of deep network. At the same time, considering the features of spatial and cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…However, the GG-Net and SegResNetVAE models performed better, achieving 82.56 % and 81.90 %, respectively. Furthermore, in the research work [40,41], additional residue and attention blocks were incorporated into the basic UNet architecture to enhance segmentation. The results showed that the Dice index value was 0.921, slightly lower than that of UNet with dense input, indicating its effectiveness and the promising use of dense and input blocks in this task.…”
Section: Discussion Of Study Results Of Cancer Segmentationmentioning
confidence: 99%
“…However, the GG-Net and SegResNetVAE models performed better, achieving 82.56 % and 81.90 %, respectively. Furthermore, in the research work [40,41], additional residue and attention blocks were incorporated into the basic UNet architecture to enhance segmentation. The results showed that the Dice index value was 0.921, slightly lower than that of UNet with dense input, indicating its effectiveness and the promising use of dense and input blocks in this task.…”
Section: Discussion Of Study Results Of Cancer Segmentationmentioning
confidence: 99%
“…U-Net is a CNN, which is basically an encoder–decoder architecture for feature extraction and localization [ 53 , 54 , 55 , 56 ]. Attention U-Net is another model that was used for segmentation purposes which introduces attention layers into the U-Net to identify and focus on relevant areas such as margins or salient features of the mass to efficiently extract features [ 57 , 58 ]. SegNet is another encoder–decoder-based architecture that can provide semantic segmentation by using skip connections and preserving contextual information, improving margin delineation capability [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…This model enhances the attention U-net network framework by incorporating residual convolution and extended residual convolution modules in the encoding path. In their work [44], utilized a residual U-Net for breast tumor segmentation, incorporating a fusion attention mechanism that combines both spatial and channel attention. In another work [45], the authors presented the RDAU-NET (Residual-Dilated-Attention-Gate-UNet) model for tumor segmentation in breast ultrasound images.…”
Section: Plos Onementioning
confidence: 99%